2017
DOI: 10.1016/j.vhri.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on Human Resource Requirement between Manual and Automated Dispensing Systems

Abstract: The ADM system decreased the workload of pharmacy technicians, whereas it required more time from pharmacists. However, the increased workload of pharmacists was associated with more comprehensive patient care functions, which resulted from the redesigned work process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…In the hybrid study, personnel savings were found of 6.5 hours/day 45. In the centralised model, the ADM system decreased the workload of pharmacy technicians but required more time from pharmacists as a result of the redesigned work process 44. The decentralised study showed reductions in MEs 42.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the hybrid study, personnel savings were found of 6.5 hours/day 45. In the centralised model, the ADM system decreased the workload of pharmacy technicians but required more time from pharmacists as a result of the redesigned work process 44. The decentralised study showed reductions in MEs 42.…”
Section: Resultsmentioning
confidence: 96%
“…The later literature search found 848 articles (duplicates not removed), of which four new articles were evaluated more closely. Studies were performed in Denmark (n=2, decentralised system), Thailand (n=1, centralised system) and Brazil (n=1, hybrid system) 42–45. Safety (n=2), time (n=2) and cost-effectiveness (n=2) were studied.…”
Section: Resultsmentioning
confidence: 99%
“…This comes from the critical status of medical supplies in care delivery and the behaviour of all supply chain stakeholders who, in order to prevent inventory shortages, tend to overstock. Overcosts and losses are major (Landry, Beaulieu, and Roy 2016) and therefore there is great potential for improvement through supply chain management (SCM) practices (Nabelsi and Gagnon 2017;Ageron, Benzidia, and Bourlakis 2018). The internal supply chain of hospitals remains the weakest link in hospitals (Landry and Philippe 2004) and the health sector is lagging behind industry as it has not been able to reap the full benefits of SCM due to their slow adoption (McKone-Sweet, Hamilton, and Willis 2005;Toba, Tomasini, and Helio Yang 2008).…”
Section: Introductionmentioning
confidence: 99%
“…7,13 In short, electronic dispensaries are deployed in hospital units with the expectation of increasing human resource efficiency and increasing the quality of drug distribution systems. 15 To increase safety, some electronic dispensers are susceptible to settings such as use of alerts when detected incomplete dose withdrawal or exchange of medication and disposition of items within the dispensary, leaving away those with a similar name or packaging. 3,14 In addition, the interface between the systems of the electronic dispensary and the hospital contributes to the increase of patient safety.…”
Section: Discussionmentioning
confidence: 99%